Domination Integrity of Splitting Graph of Path and Cycle. (16th January 2013) - Vaidya, Samir K.; Kothari, Nirang J.
Abstract : If S is a dominating set of a connected graph G then the domination integrity is the minimum of the sum of two parameters, the number of elements in S and the order of the maximum component of G − S . We investigate domination integrity of splitting graph of path P n and cycle C n . This work is an effort to relate network expansion and vulnerability parameter.